Relevansi antara norma adat dan syariah dalam perkawinan: Studi kasus di Desa Huraba Siabu Mandailing - Ritonga, Raja; Roisuddin Ritonga, Ahmad (Asy-Syari’ah : Jurnal Hukum Islam, 2024)
In Mandailing society, the marriage process is closely related to a highly complex social interaction, where customary norms and Sharia law often interact simultaneously in its implementation process. In the view of Mandailing society in the village of Huraba Siabu, the implementation of marriage is not merely the execution of the Sharia contract, but also involves adherence to various customary rituals. This study aims to explore the relevance between customary norms and Sharia law in the context of marriage, with a focus on a case study in the village of Huraba Siabu, Mandailing. Through a qualitative approach, data were collected through in-depth interviews and participatory observation, followed by descriptive analysis. The study concludes that customary norms and Sharia law often complement each other and sometimes conflict in the practice of marriage in the village of Huraba Siabu, Mandailing. These findings underscore the importance of understanding the dynamics of interaction between customary norms and Sharia law in the context of marriage in rural communities. Therefore, a shift in societal paradigms regarding the interaction between customary norms and Sharia law occurs alongside changes and developments over time.